292 Separate Metastatic Foci of Squamous Cell Carcinoma and Adenocarcinoma Consider Primary High-Grade Urothelial Carcinoma. (11th January 2018) - Zafar, Rabia; Khan, Farhan; Hassan, Muhammad Masood; Naab, Tammey
Abstract: Malignant transformation of urothelial mucosa most often gives rise to conventional urothelial carcinoma, which may show a wide variety of morphological patterns such as micropapillary, plasmacytoid, nested, and microcystic variants. However, high-grade urothelial carcinoma may also display divergent differentiation to squamous cell carcinoma and adenocarcinoma. We report a case of an 82-year-old African-American man with an enlarging left renal mass and a history of metastatic carcinoma to the liver and thoracic spine, diagnosed one year ago. The liver biopsy had revealed invasive poorly differentiated adenocarcinoma. Metastatic squamous cell carcinoma involved bone from T2 and adjacent soft tissue. A biopsy of the left renal mass one year ago had revealed findings consistent with squamous cell carcinoma. During the present admission, an ultrasound-guided biopsy of the left renal mass showed malignant cells with occasional glandular differentiation and intracytoplasmic vacuoles suggestive of adenocarcinoma. They were strongly and diffusely positive for thrombomodulin, GATA3, p63, and CK7; the immunoprofile was consistent with urothelial origin. RCC immunostain was not expressed by the malignant cells; this finding ruled against a primary renal cell malignancy. These features were consistent with high-grade urothelial carcinoma arising in the renal pelvis, showing divergent differentiation. The renal pelvis is the site of origin of urothelial carcinoma in kidney. It is important to consider that high-grade urothelial carcinoma can arise in the renal pelvis without clinical manifestations of hematuria and urinary obstruction, and can demonstrate divergent differentiation including adenocarcinoma and squamous cell carcinoma. The differential diagnosis of separate metastatic foci with differing histologies should include high-grade urothelial carcinoma with origin in the renal pelvis.